Angelicin Alleviates Post-Trauma Osteoarthritis Progression by Regulating Macrophage Polarization via STAT3 Signaling Pathway - Tian, Zhansong; Zeng, Fanchun; Zhao, Chunrong; Dong, Shiwu (Frontiers in Pharmacology, 2021)
Post-trauma osteoarthritis (PTOA) is the most common articular disease characterized by degeneration and destruction of articular cartilage (Bultink and Lems, Curr. Rheumatol Rep., 2013, 15, 328). Inflammatory response of local joint tissue induced by trauma is the most critical factor accelerating osteoarthritis (OA) progression (Sharma et al., 2019; Osteoarthritis. Cartilage, 28, 658–668). M1/M2 macrophages polarization and repolarization participates in local inflammation, which plays a major role in the progression of OA (Zhang et al., 2018; Ann. Rheum. Dis., 77, 1524–1534). The regulating effect of macrophage polarization has been reported as a potential therapy to alleviate OA progression. Synovitis induced by polarized macrophages could profoundly affect the chondrocyte and cartilage matrix (Zhang et al., 2018; Ann. Rheum. Dis., 77, 1524–1534). Generally, anti-inflammatory medications widely used in clinical practice have serious side effects. Therefore, we focus on exploring a new therapeutic strategy with fewer side effects to alleviate the synovitis. Angelicin (ANG) is traditional medicine used in various folk medicine. Previous studies have revealed that angelicin has an inhibitory effect on inflammation (Wei et al., 2016; Inflammation, 39, 1876–1882), tumor growth (Li et al., 2016; Oncology reports, 36, 3,504–3,512; Wang et al., 2017; Molecular Medicine Reports, 16, 5441–5449), DNA damage (Li et al., 2019; Exp. Ther. Med., 18, 1899–1906), and virus proliferation (Li et al., 2018; Front. Cell. Infect. Microbiol., 8, 178). But its specific effects on influencing the process of OA were rarely reported. In this study, the molecular mechanism of angelicin in vivo and in vitro was clearly investigated. Results showed that angelicin could regulate the M1/M2 ratio and function and alleviate the development of PTOA in the meanwhile. Bone marrow monocytes were isolated and induced by macrophage colony-stimulating factor (M-CSF), lipopolysaccharide (LPS) and interferon (IFN)-γ for M1 polarization and interleukin (IL)-4/IL-13 for M2 polarization. Subsequently, repolarization intervention was performed. The results indicate that angelicin can repolarize M1 toward M2 macrophages by upregulating the expression of CD9. Besides, angelicin can also protect and maintain M2 polarization in the presence of LPS/IFN-γ, and subsequently downregulate the expression of inflammatory mediators such as IL-1β and TNF-α. Mechanistically, angelicin can activate the p-STAT3/STAT3 pathway by conducting CD9/gp130 to repolarize toward M2 macrophages. These results suggest angelicin can alleviate the progression of OA by regulating M1/M2 polarization via the STAT3/p-STAT3 pathway. Therefore, angelicin may have a promising application and potential therapeutic value in OA clinical treatment.